Performance evaluation of Vietnamese industrial goods and services during and post-COVID-19 era based on multi-criteria decision-making methods - Chia-Nan Wang; Tram Thi Mai Nguyen; Nhat-Luong Nhieu; Yu-Chi Chung (PLoS ONE, 2025)
The industrial goods and services sector is crucial for the advancement of the Vietnamese economy in terms of its substantial economic contribution and positive impact on employment. Performance evaluation has become critical in this industry, which has constantly developed and had an intensive rivalry. This paper aims to analyze the performance of industrial goods and services firms during and after COVID-19 using an objective integrated multi-criteria decision-making technique. This study suggests a three-phase model. Criteria Importance Through Intercriteria Correlation (CRITIC) eliminates human judgment errors, increases accuracy, and maintains objectivity in the evaluation variable weighting phase. Then, Evaluation based on Distance from Average Solution (EDAS) and Technique of Order Preference Similarity to the Ideal Solution (TOPSIS) are used as effective cross-validation techniques to evaluate and rank forty-five Vietnam Stock Exchanges-listed firms for each year from 2020 to 2022. The reliability of the CRITIC-based weights is verified by the Statistical Variance Procedure. The research results reveal that the debt term structure is the most vital among the fifteen financial research indicators reflecting a business’s solvency, profitability, growth, operating efficiency, and capital structure. Additionally, the research findings indicate discrepancies in the rankings produced by EDAS and TOPSIS. However, the disparities are not grave, and the top and bottom positions, in particular, remain consistent between the two approaches. PDN was the best firm during COVID-19 and was succeeded by CIA after the pandemic. Pursuing digital transformation, sustainable development, and keeping inventory turnover at high levels are common characteristics of successful businesses in this industry. For the first time, the article provides a performance analysis of Vietnamese industrial goods and services firms. It is a significant reference for domestic and international investors in portfolio selection, financial institutions in loan approval, managers and policymakers in planning and policy development, and researchers conducting investigations within this domain.